The role of financial planning in directing public spending with reference to iraq for the period (2004-2021) - Khalid, Dilshad; Nehme, Samir; Saleh, Bahram (Humanities Journal of University of Zakho, 2024)
The study aims to review the theoretical aspect of both financial planning and public spending and to shed light on the analysis of public spending directives according to the financial plan in Iraq for the period 2004-2021. Additionally, it endeavors to conduct future scenarios for financial planning policy in directing public spending to target non-oil GDP in Iraq until the year (2030). The study used the descriptive approach in the theoretical aspect and the deductive approach in the applied aspect to ascertain the role of financial planning in directing public spending to target the non-oil gross domestic product in Iraq. The study’s most significant findings are the development of the targeted non-oil GDP at growth rates of (5%) and (10%), alongsidewith the current and investment spending. The study revealed that the non-oil output increased in correlation with the growth of investment spending at rates exceeding several times the growth of current spending. The study proposed the formulation of future scenarios to rectify the Iraqi economy through reforming public spending, directing it towards economic sectors that are favourable to growth and economic stability.